2018
DOI: 10.3390/ma11010157
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Novel Quercetin Titanium Dioxide-Decorated Multi-Walled Carbon Nanotubes Nanocomposite on Bacillus subtilis Biofilm Development

Abstract: The present work was targeted to design a surface against cell seeding and adhering of bacteria, Bacillus subtilis. A multi-walled carbon nanotube/titanium dioxide nano-power was produced via simple mixing of carbon nanotube and titanium dioxide nanoparticles during the sol-gel process followed by heat treatment. Successfully, quercetin was immobilized on the nanocomposite via physical adsorption to form a quercetin/multi-walled carbon nanotube/titanium dioxide nanocomposite. The adhesion of bacteria on the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Hydrophobic properties and a positive charge of QPEI increase its antibacterial activity [47]. Adding titanium dioxide NPs also prevents microorganism adhesion and biofilm formation by increasing the hydrophilic activity of materials [48]. Silica NPs could also increase the flexural strength, thermal and strength stability of materials [49] Gerasymchuk et al confirmed the antimicrobial activity of graphite oxide‐based composite containing silver NPs.…”
Section: Advances In Nanomaterials and Nanotechnologies In Endodenticsmentioning
confidence: 99%
“…Hydrophobic properties and a positive charge of QPEI increase its antibacterial activity [47]. Adding titanium dioxide NPs also prevents microorganism adhesion and biofilm formation by increasing the hydrophilic activity of materials [48]. Silica NPs could also increase the flexural strength, thermal and strength stability of materials [49] Gerasymchuk et al confirmed the antimicrobial activity of graphite oxide‐based composite containing silver NPs.…”
Section: Advances In Nanomaterials and Nanotechnologies In Endodenticsmentioning
confidence: 99%
“…The efforts made to develop successful coatings which are capable of warding off implant infections have multiplied over the years [10,11,12]. In view of the decreasing efficacy of antibiotic substances against populations of bacteria which are increasingly drug-resistant, attention has been directed toward alternative antibacterial bioactive principles, including disinfectant molecules [13,14], metal ions and nanoparticles [15], nanocomposites [16], phytochemicals [17], and antimicrobial peptides [18].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, anti-infective properties have been conferred to implants by immobilizing on their surface active metals, nitric oxide (NO)-releasing materials, or non-antibiotic antibacterial substances in order to avoid the development of multiresistant bacterial strains [11]. Nanotechnology is opening up new frontiers in the design of anti-infective surfaces [12,13,14,15]. The application of metals and metal oxides, such as Ag, Au and ZnO, in the form of nanometric-sized particles as antimicrobial coatings is steadily increasing due to a series of distinctive features of such nanomaterials, including a high surface area and chemical reactivity, which allows high bioactivity, even in small doses [16].…”
Section: Introductionmentioning
confidence: 99%